PROFESIONALISME GURU DI ERA ARTIFICIAL INTELLIGENCE: REKONSTRUKSI CIRI-CIRI PROFESI DALAM TRANSFORMASI PENDIDIKAN ABAD KE-21 - Dani Oktarian; Siti Aimah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the transformation of teacher professionalism in the era of Artificial Intelligence (AI), reconstruct the characteristics of the teaching profession, and identify adaptation strategies needed to face the challenges of 21st-century education. The study used a qualitative approach with a case study design conducted at MAN 4 Banyuwangi. Research informants consisted of madrasah principals, teachers, and education personnel selected through purposive sampling techniques. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing and verifying conclusions. The results show that teacher professionalism has undergone a significant transformation through strengthening digital competencies, utilizing AI technology in the learning process, and changing the role of teachers from primary sources of knowledge to facilitators, mentors, and learning directors. In addition, the use of AI requires strengthening professional ethics, digital literacy, and critical thinking skills in educational practice. The research findings confirm that continuous adaptation to technological developments is a crucial factor in improving the quality of learning and strengthening teacher professionalism in the digital era.